Psychological readiness to return to sport after anterior cruciate ligament reconstruction in the adolescent athlete - Webster, K. E.; Feller, J. A. (Journal of Athletic Training, 2022)
Context Psychological readiness to return to sport has been shown to be associated with future play after anterior cruciate ligament (ACL) reconstruction surgery but has not been extensively studied in adolescent athletes.